Optimization on permutations: related structures, problems interrelation, heuristic compositions, applications - Miatselski, Mikalai (Technical Sciences, 2017)
A heuristics based approach to practical solving theoretically intractable combinatory and network problems is discussed. Compound heuristics (heuristics compositions) are suggested to be more efficient procedures for real size problem instances. Some aspects of the heuristics compositions topic are illustrated by optimum permutation problems. We describe a uniform presentation of the chief types of the problems and their interrelations, including the relation “to be a special case of a problem”. We consider a number of algebraic structures and combinatory constructions on permutation sets and present an inclusion chain of these constructions. The chain enables us to establish and clarify many interrelations for the minimum permutation problems, with algorithmic and complexity aspects taken into account. We also concern the applications of some problems as well.